2023
DOI: 10.3390/v15030655
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Ubiquitin-Mediated Signaling Pathway Exhibit Broad-Spectrum Antiviral Activities against New World Alphaviruses

Abstract: New World alphaviruses including Venezuelan Equine Encephalitis Virus (VEEV) and Eastern Equine Encephalitis Virus (EEEV) are mosquito-transmitted viruses that cause disease in humans and equines. There are currently no FDA-approved therapeutics or vaccines to treat or prevent exposure-associated encephalitic disease. The ubiquitin proteasome system (UPS)-associated signaling events are known to play an important role in the establishment of a productive infection for several acutely infectious viruses. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…We also show that E3 ligase activity is required for TRIM32-mediated inhibition of VEEV. However, we could not assess whether UPS inhibitors can subvert TRIM32-mediated inhibition of VEEV, because the host UPS also required for virus infection [ 19 , 21 ]. Previous study reported that TRIM32 mutants R394H and D487N lost monoubiquitination feature, but still remain the ability to self-associate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also show that E3 ligase activity is required for TRIM32-mediated inhibition of VEEV. However, we could not assess whether UPS inhibitors can subvert TRIM32-mediated inhibition of VEEV, because the host UPS also required for virus infection [ 19 , 21 ]. Previous study reported that TRIM32 mutants R394H and D487N lost monoubiquitination feature, but still remain the ability to self-associate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the host ubiquitin proteasome system (UPS) plays a crucial role in alphaviruses infection. Specifically, the post-entry stages of alphaviruses can be disrupted by UPS inhibitors, such as proteasome inhibitors and deubiquitinating enzyme inhibitors [19][20][21]. To date, only a few E3 ubiquitin ligases (E3) and deubiquitinases (DUB) have been identified as host factor or restriction factor for alphaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…This compound also possessed the highest cytotoxicity among the examined compounds (Figure 2). This compound may have further application prospects due to its demonstrated antitumor and antiviral activity, including the inhibition of the growth of implanted human tumors without causing toxic effects in mice [26,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Negative-strand synthesis was performed as previously described [23]. cDNA was generated using a specific primer to negative-strand RNA for VEEV TC-83, which contained a T7 promoter sequence attached at the 5 ′ end (T7-TC83-Neg 5 ′ -GCGTAATACGACTCACTAT ATCCGTCAGCTCTCTCGCAGG-3 ′ ).…”
Section: Negative-strand Rt-qpcrmentioning
confidence: 99%